OCENIANIE UCZNIÓW ZE SPECJALNYMI POTRZEBAMI EDUKACYJNYMI WE WŁĄCZAJĄCEJ EDUKACJI OBCOJĘZYCZNEJ W POLSCE - Jaworska, Mariola (Neofilolog, 2020)
For the last decade or so we have observed a visible increase in the interest of educational and scientific circles in Poland in actions to include children and teenagers with special educational needs in education in mainstream schools. Such children and teenagers require special support in the learning and teaching of foreign languages, well-considered selection of teaching methods and forms, and organisation of lessons, which takes account of the individual characteristics of the learners. Appropriate evaluation of their achievements is very important in working with such persons. The article presents assumptions relating to and possibilities of individualised evaluation of students with special educational needs from the perspective of inclusive foreign language education.